A comparative evaluation of nutritional properties, antioxidant capacity and physical characteristics of cabbage (Brassica oleracea var. Capitate var L.) subjected to different drying methods. (30th March 2020) - Xu, Yayuan; Xiao, Yadong; Lagnika, Camel; Li, Dajing; Liu, Chunquan; Jiang, Ning; Song, Jiangfeng; Zhang, Min
Highlights: Six drying methods (HAD, FD, MVD, VD, MVD + VD, MVD + HAD) were used to dry cabbages. Different drying methods had significant influences on quality of dried cabbages. Combined drying methods showed better nutrient retention than individual HAD. MVD + HAD products showed higher rehydration capacity compared to that of HAD. MVD + HAD performed more uniform honeycomb porous structure than individual HAD. Abstract: Cabbag has been considered as one of attractive raw materials for dehydrated vegetables owing to high nutrient value. However, information about how drying methods affect the physicochemical properties of cabbage is limited. In present study, segmented cabbages were subjected to freeze drying (FD), hot air drying (HAD), microwave vacuum drying (MVD), vacuum drying (VD), MVD combined with HAD (MVD + HAD) and VD (MVD + VD). Dehydrated cabbages were compared in terms of nutritional components, antioxidant activity, microstructure, texture and so on. Results demonstrated that HAD conducted a worse effect, with loss rate of nutritional components >45%. However, two combined methods performed higher retention for nutritional compositions, better antioxidant activity and lower energy consumption than individual HAD. Furthermore, MVD + HAD products exhibited higher rehydration capacity and more uniform honeycomb porous structure but lower hardness compared to HAD. This conclusion would be fundamental for choosing more appropriate drying methods to obtain desirable quality.